BCL‐XL exerts a protective role against anemia caused by radiation‐induced kidney damage. (25th November 2020) - Brinkmann, Kerstin; Waring, Paul; Glaser, Stefan P; Wimmer, Verena; Cottle, Denny L; Tham, Ming Shen; Nhu, Duong; Whitehead, Lachlan; Delbridge, Alex RD; Lessene, Guillaume; Smyth, Ian M; Herold, Marco J; et al.
Abstract: Studies of gene‐targeted mice identified the roles of the different pro‐survival BCL‐2 proteins during embryogenesis. However, little is known about the role(s) of these proteins in adults in response to cytotoxic stresses, such as treatment with anti‐cancer agents. We investigated the role of BCL‐XL in adult mice using a strategy where prior bone marrow transplantation allowed for loss of BCL‐XL exclusively in non‐hematopoietic tissues to prevent anemia caused by BCL‐XL deficiency in erythroid cells. Unexpectedly, the combination of total body γ‐irradiation (TBI) and genetic loss of Bcl‐x caused secondary anemia resulting from chronic renal failure due to apoptosis of renal tubular epithelium with secondary obstructive nephropathy. These findings identify a critical protective role of BCL‐XL in the adult kidney and inform on the use of BCL‐XL inhibitors in combination with DNA damage‐inducing drugs for cancer therapy. Encouragingly, the combination of DNA damage‐inducing anti‐cancer therapy plus a BCL‐XL inhibitor could be tolerated in mice, at least when applied sequentially. SYNOPSIS: The pro‐survival BCL‐2 family member BCL‐XL is critical for the survival of renal proximal tubular epithelial cells during radiation therapy in cancer patients. Genetic loss of BCL‐XL, but not its pharmacological inhibition, causes fatal kidney damage and secondary anemia in adult mice after total body irradiation. Inducible loss of BCL‐XL in all cells in adult mice causes primary anemia due to apoptosis of erythroid and megakaryocytic cell populations. γ‐radiation and BCL‐XL deficiency in all non‐hematopoietic cells cause secondary anemia resulting from kidney damage. γ‐radiation or DNA damage‐inducing drugs in combination with specific BCL‐XL inhibitor A1331852 is tolerated in mice. Abstract : Genetic loss of anti‐apoptotic BCL‐XL causes fatal kidney damage and secondary anemia in adult mice subjected to total body irradiation.